Photoassisted Surface Modification with Zwitterionic Phosphorylcholine Polymers for the Fabrication of Ideal Biointerfaces - Iwasaki, Yasuhiko (Langmuir : the ACS journal of surfaces and colloids, 2023)
Surface modification using zwitterionic 2-methacryloyloxyethyl phosphorylcholine (MPC) polymers is commonly performed to fabricate interfaces that reduce nonspecific fouling by biomolecules and cells. Accordingly, several clinically used devices, such as guide wires, stents, oxygenators, left ventricular assist devices, and microcatheters have been modified using MPC polymers. The specific types of surface modifications vary across substrates and applications. Recently, photoreactions have garnered attention for surface modification due to their stability and tunability. This review highlights various studies that employed photoreactions to modify surfaces using MPC polymers, especially photoinduced graft polymerization of MPC. In addition to antifouling materials, several micromanipulated, long-lasting hydrophilic, and super antiwear surfaces are summarized. Furthermore, several photoreactive MPC polymers that can be used to control interactions between biomolecules and materials are presented along with their potential to form selective recognition surfaces that target biomolecules for biosensors and diagnostic devices